2006
DOI: 10.1111/j.1460-9568.2006.04827.x
|View full text |Cite
|
Sign up to set email alerts
|

Early midline interactions are important in mouse optic chiasm formation but are not critical in man: a significant distinction between man and mouse

Abstract: The optic chiasm is one of the most popular models for studying axon guidance. Here axons make a key binary decision either to cross the midline to innervate the contralateral hemisphere or to remain uncrossed. In rodents, midline interactions between axons from the two eyes are critical for normal development, as early removal of one eye systematically disrupts hemispheric projections from the remaining eye, increasing the crossed projection at the expense of the uncrossed. This is similar to the abnormal dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
21
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 65 publications
(97 reference statements)
6
21
0
Order By: Relevance
“…In binocularly intact rodents, retinal fibres mingle within the chiasm prior to projecting to either hemisphere. Axon guidance is considered to rely on this mingling and abnormal projections occur when retinal fibres from one eye are lacking (Neveu et al, 2006). In primates, enucleation is thought to have no impact on the remaining eye's projections since retinal projections are spatially segregated and no mingling occurs (Taylor and Guillery, 1995; Jeffery et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In binocularly intact rodents, retinal fibres mingle within the chiasm prior to projecting to either hemisphere. Axon guidance is considered to rely on this mingling and abnormal projections occur when retinal fibres from one eye are lacking (Neveu et al, 2006). In primates, enucleation is thought to have no impact on the remaining eye's projections since retinal projections are spatially segregated and no mingling occurs (Taylor and Guillery, 1995; Jeffery et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…One study found a ratio of 53:47 for crossed versus uncrossed projections in a late enucleated man (Kupfer et al, 1967), which is less asymmetrical than that found for binocularly intact human and non-human primates (~ 58:42) (Chacko, 1948; Horton, 1997). Lastly, anophthalmic patients born with only one eye exhibit symmetrical visual evoked potentials (VEPs) in visual cortex, reflecting an equal decussation of retinal fibres at the chiasm (Neveu et al, 2006). Therefore, an unequal number of nasal versus temporal retinal projections to the visual system cannot completely account for the asymmetries observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, our findings in embryonic Tupaia belangeri provide new evidence of diversity in the chiasmatic architecture of placental mammals. Because ipsilaterally projecting axons in higher primates, as in Tupaia belangeri, are confined to lateral parts of the chiasm (Jeffery et al, 1998;Neveu et al, 2006; present results; for reviews see Jeffery and Erskine, 2005;Neveu and Jeffery, 2007), Tupaia belangeri is a promising candidate model for future studies in this field. These studies will first address whether in fact and how presumed glial guideposts interact with ganglion cell axons destined to project ipsilaterally, an unresolved question also in marsupials.…”
Section: Conclusion and Open Questionsmentioning
confidence: 87%
“…Unexpectedly, these two types of chiasmatic organization do not represent distinctive features of marsupial and eutherian (placental) mammals. Instead, in the newborn and adult tree shrew Tupaia belangeri (Tupaiidae, Scandentia, Euarchontoglires, Eutheria, Theria, Mammalia) as well as in higher primates and probably in man, ipsilaterally projecting axons, such as are found in marsupials, are confined to lateral parts of the chiasm (Jeffery et al, 1998;Neveu et al, 2006; for reviews see Jeffery and Erskine, 2005;Neveu and Jeffery, 2007). Hence, "caution should be exercised when attempting to extrapolate from rodents to higher mammals" (Neveu et al, 2006).…”
mentioning
confidence: 97%
“…In this respect it is of interest that the mechanisms which determine axonal guidance at the chiasm appear to differ between humans and mouse, indicating the presence of more than one developmental strategy in mammals. 12 The above findings may have implications not only for foveal development itself, but also for the position in the fundus at which the fovea develops. The vertical meridian is defined by the position of the fovea at the posterior pole because this is the normal determinant of fixation.…”
mentioning
confidence: 94%